Spatio-temporal variation in pollen limitation and reproductive success of two scape morphs in Primula farinosa - Vanhoenacker, Didrik (The New phytologist, 2006)
In plant populations where reproductive output is limited by pollinator visitation, plants with attractive floral displays should have a selective advantage. We examined the effect of inflorescence height on pollination success in Primula farinosa, which is dimorphic for scape length. To test the hypothesis that fruit and seed initiation are more strongly pollen-limited in the short-scaped than in the long-scaped morph, and that this difference is affected by spatio-temporal variation in pollen limitation, we conducted a hand-pollination experiment in four populations over 2 yr. Pollen limitation of fruit initiation varied among populations and years, and was stronger in the short-scaped than in the long-scaped morph. The results suggest that interactions with pollinators will need to be considered for a full understanding of the maintenance of this striking polymorphism. The study also shows that, although pollen limitation is likely to vary in space and time in many plant species, such variation is not necessarily associated with variation in selection on floral characters